Model of Junior High School Students' Pencak Silat Upright Sweep Technique Skills Using Inflatable Punching Bag Media - Saputra, William; Lubis, Johansyah; Juniarto, Mastri; Rihatno, Taufik (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. This study aims to develop a Pencak Silat vertical sweep technique skill model based on the Inflatable Punching Bag media for junior high school students, as vertical sweep falls are highly effective in securing the highest points in pencak silat competitions. Materials and Methods. This study demonstrates its utility in Developing a skill model for the vertical sweep technique in Pencak Silat using Inflatable Punching Bag media aimed at junior high school students. This model serves as a resource for coaches in training athletes at junior high school Pencak Silat programs and extracurricular activities, while also providing coaches with additional training tools to enhance their sessions. This study involves a systematic approach utilizing the ADDIE model, which is commonly employed in the creation of training frameworks. It encompasses essential stages of straightforward training design, consisting of five phases: Analysis, Design, Development, Implementation, and Evaluation. Results. The final result of the Pencak Silat vertical sweep technique skill model utilizing Inflatable Punching Bag media for junior high school students, following the research conducted, can be concluded that the study... This initiative successfully produces an 18-skill model technique focused on upright martial arts, utilizing an inflatable punching bag designed for junior high school students. Conclusions. This study effectively created 18 skill models for the Pencak Silat upright sweep technique utilizing Inflatable Punching Bag media, specifically designed for junior high school students. This model serves as a comprehensive training guide for coaches, offering a range of effective tools designed to enhance upright sweep technique skills during matches.